ALI SYARI’ATI’S PERSPECTIVE OF HUMANISM VALUE IN DIWAN SAYYID QUTHB - Himatul Istiqomah; Kisno Umbar (Universitas Negeri Malang, 2019)
Among the many interpretations and claims of humanism by some ideologies, Islam provides its view more comprehensively. Man on earth is seen as a caliph (al-Baqarah [2]: 30), without losing the aspect of divinity. Based on the understanding of Ali Syari’ati’s humanism, researchers seek to uncover the values of humanism contained in Diwan Sayyid Qutb (the work of Islam reformer and social activist, Sayyid Qutb (d. 1966)) and explain how the delivery. The goal is realized through a descriptive qualitative approach, with qualitative content analysis of the latest version of Mayring.The results of this study indicate that the poems in Diwan Sayyid Qutb were analyzed (‘Asyiq al-Muhal, al-Ka’su al-Masmumah, al-Zad al-Akhir, and Shaut al-Wathaniyah) loaded with the values of humanism, among them: religious values, optimistic, moral, consciousness, freedom, creative, and social values. The delivery tends to use simple language and not metaphors. Some poems are closely related to personality and social life poet. As an Islam reformer, his poems are identical to religious values.